Algorithme evolutionnaire (AE) pour l'optimisation des debits sur les reseaux hydrauliques a la demande - Nouiri I.; Lebdi F.; Lamaddalena N. (Irrigation systems performance, 2005)
This paper presents the development of an Evolutionary Algorithm (EA) for flow optimisation in water systems. The aim is to reduce and stabilise the maximum flow produced. The model was used to calculate the optimal inflows for the seven tanks of the studied water distribution system. The regulation scenario proposed by the optimisation model is characterised by two inflow values. It gives the best arrangement between the maximum source flow produced and the maximum constraints violations. This scenario reduces the maximum produced flow by 17.9 percent, and also the maximum violations of tolerable water levels to acceptable values. The optimal solution guarantee better flow stability for water source than the initial situation.
2. WASAMED Workshop: Irrigation Systems Performance, 2004/06/24-28, Hammamet (Tunisia)